Strategi Kreatif Sebagai Urat Nadi Periklanan - Basnendar Herry Prilosadoso (Ornamen, 2007)
Advertising couldn’t separate from human life for almost people believe that advertising become to their life style. Advertising likes social texts that use to understanding the dinamiced of sociaty from one part to another part when the advertise opened. Creativity aspect from advertising is the most important thing to create a new advertise that depand on the visual communication design principles. So, how to appear creativity of advertising with visual communication design media until done to the audience.Key words : Advertising, Design, Creativy.